Phylogeographic and genetic network assessment of COVID-19 mitigation protocols on SARS-CoV-2 transmission in university campus residencesResearch in context - Joel O. Wertheim; Tetyana I. Vasylyeva; Robert J. Wood; Kalen Cantrell; Soraya Piña Contreras; Aryeh Feldheim; Ravi Goyal; Jennifer L. Havens; Rob Knight; Louise C. Laurent; Niema Moshiri; Robert Neuhard; et al. (EBioMedicine)
Summary: Background: Congregate living provides an ideal setting for SARS-CoV-2 transmission in which many outbreaks and superspreading events occurred. To avoid large outbreaks, universities turned to remote operations during the initial COVID-19 pandemic waves in 2020 and 2021. In late-2021, the University of California San Diego (UC San Diego) facilitated the return of students to campus with comprehensive testing, vaccination, masking, wastewater surveillance, and isolation policies. Methods: We performed molecular epidemiological and phylogeographic analysis of 4418 SARS-CoV-2 genomes sampled from UC San Diego students during the Omicron waves between December 2021 and September 2022, representing 58% of students with confirmed SARS-CoV-2 infection. We overlaid these analyses across on-campus residential information to assess the spread and persistence of SARS-CoV-2 within university residences. Findings: Within campus residences, SARS-CoV-2 transmission was frequent among students residing in the same room or suite. However, a quarter of pairs of suitemates with concurrent infections had distantly related viruses, suggesting separate sources of infection during periods of high incidence in the surrounding community. Students with concurrent infections residing in the same building were not at substantial increased probability of being members of the same transmission cluster. Genetic network and phylogeographic inference indicated that only between 3.1 and 12.4% of infections among students could be associated with transmission within buildings outside of individual suites. The only super-spreading event we detected was related to a large event outside campus residences. Interpretation: We found little evidence for sustained SARS-CoV-2 transmission within individual buildings, aside from students who resided in the same suite. Even in the face of heightened community transmission during the 2021–2022 Omicron waves, congregate living did not result in a heightened risk for SARS-CoV-2 transmission in the context of the multi-pronged mitigation strategy. Funding: SEARCH Alliance: Centers for Disease Control and Prevention (CDC) BAA (75D301-22-R-72097) and the Google Cloud Platform Research Credits Program. J.O.W.: NIH–NIAID (R01 AI135992). T.I.V.: Branco Weiss Fellowship and Newkirk Fellowship. L.L.: University of California San Diego.